Experimental and Modeling Analyses of Human Motion Across the Static Magnetic Field of an MRI Scanner - Gurrera, Davide; Leardini, Alberto; Ortolani, Maurizio; Durante, Stefano; Caputo, Vittorio; Gallias, Karmenos K.; Abbate, Boris F.; Rinaldi, Calogero; Iacoviello, Giuseppina; Acri, Giuseppe; Vermiglio, Giuseppe; Marrale, Maurizio (Frontiers in Bioengineering and Biotechnology, 2021)
It is established that human movements in the vicinity of a permanent static magnetic field such as those in magnetic resonance imaging (MRI) scanners induce electric fields in the human body; this raises potential severe risks of health to radiographers and cleaners exposed routinely to these fields in MRI rooms. The relevant directives and parameters, however, are based on theoretical models, and accurate studies on the simulation of the effects based on human movement data obtained in real conditions are still lacking. Two radiographers and one cleaner, familiar with MRI room activities and these directives, were gait analyzed during the execution of routine job motor tasks at different velocities. Full body motion was recorded in a gait laboratory arranged to reproduce the workspace of a room with an MRI full-body scanner. Body segments were tracked with clusters of at least three markers, from which position and velocity of the centroids were calculated. These were used as input in an established computer physical model able to map the stray field in an MRI room. The spatial peak values of the calculated electric field induced by motion of the head and of the entire body during these tasks, for both the health and sensory effects, were found smaller than the thresholds recommended by the European directives, for both 1.5 T and 3.0 T MRI. These tasks therefore seem to guarantee the safety of MRI room operators according to current professional good practice for exposure risks. Physical modelling and experimental measures of human motion can support also occupational medicine.